Electron Structures in Titan's Induced Magnetosphere and Low‐Frequency Wave Activity - Kim, Konstantin (2025)
The interaction of Titan´s ionosphere with Saturn´s magnetosphere leads to a mix of perturbed electromagnetic fields and accelerated and thermalized plasma in the induced magnetosphere. The complexity of this region has been noted in previous studies. However, many local structures and processes have not been studied and addressed in detail before. In this case study, we examine the origin of quasi-periodic plasma structures in Titan´s induced magnetosphere observed during the T36 flyby. We use data from the electron and ion spectrometers CAPS/ELS and IMS, the RPWS Langmuir probe and electric antenna, and the fluxgate magnetometer (MAG) to analyze plasma parameters, for example, density and temperature and magnetic field fluctuations, to characterize the processes involved. The observed plasma structures are quasi-periodic on a scale of about 20 s (or local ion gyroperiod) and possess acceleration signatures from a few eV up to 700 eV. A burst of low-frequency (around the ion-cyclotron and lower-hybrid frequency) and low-amplitude (${B}_{bg}approx 7$ nT, $delta B/B_{bg}approx $ 0.14) waves are observed in the proximity of the plasma structures. We discuss possible mechanisms leading to the development of the observed plasma structures, for example, magnetohydrodynamics instabilities and the contribution of the local electric fields.